The development of an evidence-based clinical checklist for the diagnosis of anterior knee pain - Dominique C. Leibbrandt; Quinette Louw (AOSIS, 2017)
Background: Anterior knee pain (AKP) or patellofemoral pain syndrome is common and may limit an individual's ability to perform common activities of daily living such as stair climbing and prolonged sitting. The diagnosis is difficult as there are multiple definitions for this disorder and there are no accepted criteria for diagnosis. It is therefore most commonly a diagnosis that is made once other pathologies have been excluded. Objectives: The aim of this study was to create an evidence-based checklist for researchers and clinicians to use for the diagnosis of AKP. Methods: A systematic review was conducted in July 2016, and an evidence-based checklist was created based on the subjective and objective findings most commonly used to diagnose AKP. For the subjective factors, two or more of the systematic reviews needed to identify the factor as being important in the diagnosis of AKP. Results: Two systematic reviews, consisting of nine different diagnostic studies, were identified by our search methods. Diagnosis of AKP is based on the area of pain, age, duration of symptoms, common aggravating factors, manual palpation and exclusion of other pathologies. Of the functional tests, squatting demonstrated the highest sensitivity. Other useful tests include pain during stair climbing and prolonged sitting. The cluster of two out of three positive tests for squatting, isometric quadriceps contraction and palpation of the patella borders and the patella tilt test were also recommended as useful tests to include in the clinical assessment. Conclusion: A diagnostic checklist is useful as it provides a structured method for diagnosing AKP in a clinical setting. Research is needed to establish the causes of AKP as it is difficult to diagnose a condition with unknown aetiology.